Digital Marketing Transformation of Zakat and Waqf Based on Maqashid Syariah to Increase Social Maslahah - Muhammad Salman Al Farisi (International Journal of Sharia Business Management, 2026)
This study aims to analyze the transformation of digital marketing in the management of zakat and waqf based on the principles of maqashid shariah in order to increase social maslahah. The research seeks to explore how digital marketing strategies can enhance the effectiveness, transparency, and accessibility of Islamic philanthropic institutions while ensuring that their operations remain aligned with the ethical objectives of Islamic law. Furthermore, the study examines how digital platforms can strengthen public participation and optimize the social impact of zakat and waqf distribution. This research employs a qualitative approach using a literature study method. Data were collected from various academic sources, including journal articles, books, institutional reports, and relevant publications related to Islamic social finance, digital marketing, and maqashid shariah. The collected data were analyzed using qualitative content analysis to identify patterns, themes, and conceptual relationships between digital marketing strategies and the objectives of Islamic philanthropic management. The results of the study indicate that the transformation of digital marketing significantly improves the efficiency and outreach of zakat and waqf institutions. Digital platforms such as social media, crowdfunding systems, and online payment applications enable institutions to communicate more effectively with the public, increase transparency, and encourage broader community participation. Moreover, the integration of maqashid shariah principles ensures that digital marketing strategies not only aim to increase fundraising but also promote social justice, welfare, and equitable distribution of resources. Consequently, the digital transformation of zakat and waqf marketing has the potential to strengthen the realization of social maslahah and contribute to sustainable socio-economic development.